Report on a survey of mammals of the Sierra Madre Range, Luzon Island, Philippines - Duya, Mariano Roy M.; Alviola, Philip A.; Duya, Melizar V.; Balete, Danilo S.; Heaney, Lawrence R. (2007)
An inventory of mammals was undertaken at 11 localities along the Sierra Madre range in 2002 to 2005, in areas where few or no data were available previously. The inventory included lowland and montane forest habitats, at elevations from 300 to 1500 m. Thirty-eight species of mammals were recorded, including nine new records for the mountain range. One species, Kerivoula cf. papillosa, had not been recorded previously from the Philippines, and one, Coelops hirsutus, was known previously only from Mindanao and Mindoro Islands. Two species, in the genera Apomys and Chrotomys, may represent previously unknown species. We captured Archboldomys musseri only on Mt. Cetaceo, supporting previous evidence that it is endemic only to that mountain. A modified mist-netting technique (V-net) for insectivorous bats was effectively used to capture these species. The new records clearly demonstrate that the mammalian fauna of the Sierra Madre is poorly known. Surveys of many additional areas are needed in all known habitat types along the Sierra Madre, especially karst, ultrabasic, and mossy forest, to fully document its diversity.
Keywords: Mammals